Assessment of the impact of motor transport on the ecological state of urbanized areas using the pollution index - Svetlana A. Novikova; Sergey M. Ugay (RUDN Journal of Ecology and Life Safety)
A new method for calculating the pollution index of urbanized areas from motor vehicles is proposed based on three parameters (air pollution, noise level, soil pollution) and the weights of each parameter in it are determined. A primary component-by-component assessment of all the indicators under consideration and subsequent calculation of the pollution index for the cities of the Irkutsk agglomeration are carried out. A scientifically based approach to the development of priority areas of environmental protection measures is proposed.